F‐block MOFs: A Pathway to Heterometallic Transuranics. Issue 5 (19th December 2022) - Park, Kyoung Chul; Kittikhunnatham, Preecha; Lim, Jaewoong; Thaggard, Grace C.; Liu, Yuan; Martin, Corey R.; Leith, Gabrielle A.; Toler, Donald J.; Ta, An T.; Birkner, Nancy; Lehman‐Andino, Ingrid; Hernandez‐Jimenez, Alejandra; et al.
Abstract: A novel series of heterometallic f ‐block‐frameworks including the first examples of transuranic heterometallic 238 U/ 239 Pu‐metal–organic frameworks (MOFs) and a novel monometallic 239 Pu‐analog are reported. In combination with theoretical calculations, we probed the kinetics and thermodynamics of heterometallic actinide(An)‐MOF formation and reported the first value of a U‐to‐Th transmetallation rate. We concluded that formation of uranyl species could be a driving force for solid‐state metathesis. Density of states near the Fermi edge, enthalpy of formation, band gap, proton affinity, and thermal/chemical stability were probed as a function of metal ratios. Furthermore, we achieved 97 % of the theoretical maximum capacity for An‐integration. These studies shed light on fundamental aspects of actinide chemistry and also foreshadow avenues for the development of emerging classes of An‐containing materials, including radioisotope thermoelectric generators or metalloradiopharmaceuticals. Abstract : Like baking cookies to personal taste, preparation of a library of heterometallic actinide‐MOFs allows for tailoring of the "flavor" of material properties. Mixing the radionuclide ingredients in proper ratios reveals structure–property relationships and unique design principles for new classes of actinide‐based materials. In addition, the prepared frameworks provide a recipe for novel, pre‐designed transuranic MOFs.